Integrative Studies on a New Ciliate Campanella sinica n. sp. (Protista, Ciliophora, Peritrichia) Based on the Morphological and Molecular Data, With Notes on the Phylogeny and Systematics of the Family Epistylididae - Wang, Zhe; Wu, Tong; Lu, Borong; Chi, Yong; Zhang, Xue; Al-Farraj, Saleh A.; Song, Weibo; Warren, Alan; Li, Lifang; Wang, Chundi (Frontiers in Microbiology, 2021)
During an investigation on freshwater peritrichs, a new colonial sessilid ciliate, Campanella sinica n. sp., was isolated from aquatic plants in an artificial freshwater pond in Qingdao, China. Specimen observations of this species were performed both in vivo and using silver staining. Campanella sinica n. sp. is characterized by the appearance of the mature colony which is up to 2 cm high and contains more than 1,000 zooids, the asymmetric horn-shaped zooids, the conspicuous and strongly everted multi-layered peristomial lip, the slightly convex peristomial disc, and the well-developed haplokinety and polykinety which make more than four circuits of the peristome before descending into the infundibulum. The SSU rDNA, ITS1–5.8S rDNA–ITS2 region, and LSU rDNA genes were sequenced and used for phylogenetic analyses which revealed that the family Epistylididae Kahl, 1933 is non-monophyletic whereas the genus Campanella is monophyletic and nests within the basal clade of the sessilids. The integrative results presented here support the assertion that the genus Campanella represents a separate lineage from other epistylidids, suggesting further revision of the family Epistylididae is needed. We revise Campanella including the transfer into this genus of a taxon formerly assigned to Epistylis which we raise to species rank, i.e., Campanella ovata (Nenniger, 1948) n. grad. & n. comb. (original combination Epistylis purneri f. ovata Nenninger, 1948). In addition, we provide a key to the identification of the species of Campanella.